The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.21203/rs.3.rs-65418/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

To What Extent Does Human Capital Development Impact Economic Growth? Empirical Evidence From Nigeria.

Abstract: This study examined the effect of human capital development on the economic growth of Nigeria. In achieving this, the human capital variables of education and health care were included in the study. The study employed the Autoregressuve and Distributive Lag (ARDL) model to annual series covering the period 1983 to 2018 for analysis. The findings of the study revealed the presence of a long-run association among the stuady variables. Further, it was discovered that in both the short and long run, both componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…The negative effect of ODA on economic growth corroborates and lends credence to earlier studies (Adedokun, 2017;Mustafa et al, 2019;Hussain et al, 2018;Niyonkuru, 2016;Pohwani et al, 2019;Quy, 2016;Tang and Bundhoo, 2017;Weerasingha and Mustafa, 2019), which established that foreign aid had a negative or insignificant impact on economic growth. Nevertheless, the result shows that the coefficient of HCD is À0.0742, with a probability value of 0.9196, which is statistically insignificant, which is in line with earlier studies (Abubakar et al, 2020;Omankhanlen et al, 2014;Tsaurai, 2017). The result indicates that the current stock of human capital in South Asia and Africa does not stimulate economic growth.…”
Section: Human Capital Interactionsupporting
confidence: 90%
See 2 more Smart Citations
“…The negative effect of ODA on economic growth corroborates and lends credence to earlier studies (Adedokun, 2017;Mustafa et al, 2019;Hussain et al, 2018;Niyonkuru, 2016;Pohwani et al, 2019;Quy, 2016;Tang and Bundhoo, 2017;Weerasingha and Mustafa, 2019), which established that foreign aid had a negative or insignificant impact on economic growth. Nevertheless, the result shows that the coefficient of HCD is À0.0742, with a probability value of 0.9196, which is statistically insignificant, which is in line with earlier studies (Abubakar et al, 2020;Omankhanlen et al, 2014;Tsaurai, 2017). The result indicates that the current stock of human capital in South Asia and Africa does not stimulate economic growth.…”
Section: Human Capital Interactionsupporting
confidence: 90%
“…Using enveloping data test, Omankhanlen et al (2014) found that between 1990 and 2011, the HCD variable impeded economic growth. The findings of Tsaurai (2017) and Abubakar et al (2020) for developing economies further deepen the argument that HCD is growth-inhibiting.…”
Section: Empirical Literaturementioning
confidence: 75%
See 1 more Smart Citation
“…Bakare et al [63] examined the extent to which banks' credit affects economic growth in Nigeria. The data used was collected from the Central Bank of Nigeria statistical bulletin for a period of 24 years from 1990 to 2013.…”
Section: Mamman and Hashimmentioning
confidence: 99%
“…A loan default occurs when the borrower does not make required payments or in one way or the other way does not adhere to the terms of a loan [11]. The study, the Extent that Bank Credit Stimulate Economic Growth revealed that the lagged value of credit to the private sector is positively and significantly influencing economic growth in Nigeria while the lagged value of credit to the public sector shows a positively insignificant relationship with GDP [12]. Also in a research, "perceived loan risk and Ex Post Default" the outcome showed that the banks screening criteria was limited by the presence of information asymmetry [13].…”
Section: Loan Performance Rate In Nigeriamentioning
confidence: 99%